Platelet inhibition by low-dose aspirin is not influenced by body mass or weight - Heffron, Sean P.; Windheim, Joseph; Barrett, Tessa J.; Voora, Deepak; Berger, Jeffrey S. (Platelets (Edinburgh), 2022)
Aspirin's clinical efficacy may be influenced by body weight and mass. Although inadequate platelet inhibition by aspirin is suggested as responsible, evidence for this in non-diabetic patients is sparse. We investigated the influence of body weight and mass on aspirin's inhibition of platelet aggregation in healthy adults without diabetes. Cohort one (NYU, n = 84) had light transmission aggregometry (LTA) of platelet-rich plasma to submaximal adenosine diphosphate (ADP) and arachidonic acid (AA) before and following 1 week of daily 81 mg non-enteric coated aspirin. Subjects in the validation cohort (Duke, n = 66) were randomized to 81 mg or 325 mg non-enteric coated aspirin for 4 weeks, immediately followed by 4 weeks of the other dose, with LTA to submaximal collagen, ADP, and AA before and after each dosage period. Body mass index (BMI) range was 18.0-57.5 kg/m 2 and 25% were obese. Inhibition of platelet aggregation was similar irrespective of BMI, body weight and aspirin dose. There was no correlation between platelet aggregation before or after aspirin with BMI or body weight. Our data demonstrate that aspirin produces potent inhibition of direct and indirect COX1-mediated platelet aggregation in healthy adults without diabetes regardless of body weight or mass - suggesting that other mechanisms explain lower preventive efficacy of low-dose aspirin with increasing body weight/mass.